Chemical composition of two-photon oxidized graphene. (May 2017) - Johansson, Andreas; Tsai, Hung-Chieh; Aumanen, Jukka; Koivistoinen, Juha; Myllyperkiö, Pasi; Hung, Yi-Zhe; Chuang, Min-Chiang; Chen, Chia-Hao; Woon, Wei Yen; Pettersson, Mika
Abstract: Chemical composition of two-photon oxidized single-layer graphene is studied by micrometer X-ray photoelectron spectroscopy (XPS). Oxidized areas with a size of 2 × 2 μm 2 are patterned on graphene by tightly focused femtosecond pulsed irradiation under air atmosphere. The degree of oxidation is controlled by varying the irradiation time. The samples are characterized by four wave mixing (FWM) imaging and Raman spectroscopy/imaging. Micrometer-XPS is used to study local chemical composition of oxidized areas. XPS imaging shows good contrast between oxidized and non-oxidized areas. Gradual oxidation is observed from growth of signals attributed mainly to hydroxyl (COH) and epoxide (COC) groups with a minor contribution of carboxylic groups. The highly oxidized areas are characterized by ∼40% of carbon atoms involved in hydroxyl and ∼25% in epoxide groups. The Raman peaks of oxidized graphene are relatively narrow indicating less disordered material than what is typically observed for graphene oxide. Graphical abstract: